PROSES KEBIJAKAN PERSUTERAAN ALAM DI SULAWESI SELATAN - Andi Sadapotto (Forestry Faculty of Universitas Hasanuddin, 2012)
Production of cocoon and raw silk in South Sulawesi have decreased in recent years. One of the problem is misleading policy formulation and implementation. The purpose of this studies is to know the policy of sericulture that have implemented in South Sulawesi. The method of analyses are discourse analysis/narrative, actors/network, and politics/interest. The result indicated that three factors ie. narrative, actors and interests among stakeholder in sericulture development disturb the policy implementation so it wouldn’t achieve the goal. Incorrect problem formulation also disrupt the sericulture development so it didn’t increase cocoon and raw silk production in South Sulawesi. Key words: policy, process, sericulture, South Sulawesi